Development and Evaluation of Complete Diet using in vitro Gas Production Technique in Semi-Arid Borno State. - Modu-kagu, H.A.; Kolo, U.M.; Girgiri, A.Y.; Asheikh, L.G.; Abbator, F.I.; Mustapha, M.; Danbaki, A.A.; Mohammed, I.D. (Nigerian Journal of Animal Science, 2026)
The study was conducted to formulate and evaluate the nutrient composition of a complete diet in semi-arid Borno State. Locally available feed resources were used to formulate five diets, and were subjected to chemical analysis and in vitro gas production. For the in vitro gas production, 200 mg of the samples were each incubated in a 100 ml glass syringes for 3, 6, 12 and 24 hours. The result of the chemical composition revealed that the dry matter content ranged from 92.35–94.30%, crude protein from 11-12%, crude fibre 30.75–39.50% and metabolisable energy from of 8.74 to 10.57 MJ. The result showed that dry matter, crude protein, ether extract, ash and metabolisable energy were not significantly (P>0.05) different. The in vitro gas production revealed that gas production at 24 h was significantly (P<0.05) different with the highest values recorded in T4 (20.000 ml) and T5 (19.000 ml), followed by T3 (15.667 ml) and T1 (16.333 ml). The higher gas production in T4 and T5 could indicate that these formulations contained substrates that were more efficiently fermented over the longer incubation period. It was concluded that T4 and T5 that have a balanced fibre content and higher levels of fermentable carbohydrates exhibited significantly higher gas production at 24 hours, suggesting more efficient microbial fermentation. This shows that optimizing fibre and energy sources will enhance ruminal fermentation in ruminants.